Selected GO TEXAN Members' Online Presence: A Communications Audit - Courtney Gibson; Chelsey Ahrens; Courtney Meyers; Erica Irlbeck (Journal of Applied Communications, 2012)
Prior research has indicated that alternative, or nontraditional, agricultural producers have more difficulty marketing their products, which may lead to them turning to online and social media tools to meet their unique marketing needs. In order to assess the extent to which alternative agriculture producers are using these communication tools, a communications audit was conducted to determine and describe how select members of the GO TEXAN network are utilizing websites and social media tools for their alternative agricultural business or company. A majority of the members included in this study were found to be using websites, while fewer were utilizing social media tools. Facebook, blogs, and Twitter were found to be the most popular social media tools used. Both website and social media content was found to be mostly general information about the company and either its products or services or marketing and advertising information. Future research should be conducted on effective methods to train businesses in employing social media and online tools for marketing, promotion, and advertising.
Keywords: websites; social media; alternative agriculture; communications audit; content analysis; GO TEXAN; online communication